Pendekatan Pendidikan Kewarganegaraan sebagai Pendidikan Karakter di Sekolah Dasar - L. Heny Nirmayani (STAHN Mpu Kuturan Singaraja, 2021)
Civic Education is general and fundamental subject. In elementary school levels, civic education had important aspect for students in terms of establishing personal citizens were able to understand and carry out the right and obligations as Indonesia citizens which are intelligent, skillful, and had a good character. Character education is related with students attitudes and behavior which aimed to build, transform, disseminate and develop the students potential by coordinating hearts, feelings, thoughts and movements in accordance with Pancasila as philosophy of life. The quality of civic education should improve by developing the student characteristic started from planning, processing/implementation, evaluating, and obstacles that will be faced up. During the implementation of civic education as character education, teachers did teaching and learning process which suitable with lesson planned integrated with character. The stages started from pre-activity, main activity, close activity, and selected the learning method which appropriate with the lessons. Evaluation of all learning process is conducted in the end of activity